IMPROVING TAXATION OF ENTERPRISES WITH PARTICIPATION OF FOREIGN INVESTMENTS IN UZBEKISTAN - Niyozov Abdunabi Olim ugli (Scholar Express Journal, 2025)
The article is devoted to the investigation of the special role of enterprises and joint ventures with participation of foreign investment in the economy of the Republic of Uzbekistan. In addition, the article analyzes some features of taxation of the activities of enterprises and joint ventures with the participation of foreign investments.
Keywords: enterprise; joint venture; investment; tax